Concentration and extraction method of sodium nitrate
Through the combination of gel water absorption technology and dissolution crystallization method, the problems of low purification efficiency, low purity and serious pollution in the existing sodium nitrate concentration and extraction methods are solved, and the efficient, energy-saving and environmentally friendly sodium nitrate concentration and extraction effect is achieved.
Patent Information
- Application Number
- CN202510029426.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The existing sodium nitrate concentration extraction method has problems such as low purification efficiency, low purity and serious pollution.
The initial concentration of sodium nitrate was performed using gel water absorption technology, and the secondary concentration was performed using a water-absorbing gel material, and the sodium nitrate crystal was precipitated by dissolution crystallization method, and crystallization was promoted using ethanol and water-absorbing materials.
It realizes efficient, energy-saving and environmentally friendly sodium nitrate concentration extraction, improves the purity and concentration of the product, simplifies the operation process, and reduces environmental pollution.
Smart Images

Figure CN119797396A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical industry, in particular to a method for concentrating and extracting sodium nitrate. Background Art
[0002] Sodium nitrate is an important chemical widely used in industrial and laboratory fields, mainly used to prepare gunpowder, fertilizer, glass, metal surface treatment and other products. However, the sodium nitrate concentration and extraction methods in the prior art have problems such as low purification efficiency, low purity, and serious pollution. The traditional evaporation concentration process has high energy consumption, and the by-product salt cannot be completely disposed of, resulting in the generation of new solid waste. Although the ion exchange method is simple to operate and has high product purity, the regeneration and consumption cost of the ion exchanger needs to be considered. Although the multi-effect evaporation technology is energy-saving, environmentally friendly, and suitable for large-scale production, it is not economical in small-scale production.
[0003] In addition, the existing sodium nitrate evaporation and crystallization system mainly adopts a single-effect evaporation process, which has high energy consumption and low crystallization efficiency. The produced crystals are prone to carry other impurities, making it difficult to obtain high-purity products. These shortcomings limit the application of sodium nitrate in fields requiring high purity. Therefore, it is particularly important to develop a new method that is efficient, environmentally friendly and can improve purity. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a method for concentrating and extracting sodium nitrate, which has the advantages of high efficiency, energy saving and environmental protection, and solves the problems of low purification efficiency, low purity and serious pollution in the prior art method for concentrating and extracting sodium nitrate.
[0006] (II) Technical solution
[0007] To achieve the above object, the present invention provides the following technical solution: a method for concentrating and extracting sodium nitrate, comprising the following steps:
[0008] Step 1, concentrating the stock solution with water-absorbing gel: preparing a water-absorbing gel device, and using the gel water-absorbing method in the device to concentrate the sodium nitrate stock solution with a mass concentration lower than 80% to 80%±0.5% to obtain a concentrated solution 1;
[0009] Step 2, secondary concentration of water-absorbing gel: using water-absorbing gel material to secondary concentrate the concentrated solution 1 to 90%±0.10% to obtain concentrated solution 2;
[0010] Step 3, dissolution crystallization to obtain sodium nitrate crystals: Sodium nitrate crystals are precipitated from the concentrated solution 2 by dissolution crystallization method, ethanol is added to the sodium nitrate solution, and when the mass concentration of the sodium nitrate solution is 95% and the alcohol-liquid ratio is 7:1, the sodium nitrate crystals are precipitated, and then a water-absorbing material is added to further precipitate the sodium nitrate crystals.
[0011] Preferably, the preparation of the water-absorbing gel device in step 1 includes: preparing an electrode sheet, testing the electrode sheet, and building a gel water-absorbing platform for analysis, wherein the process of preparing the electrode sheet is:
[0012] S1.1, the porous carbon was subjected to SEM scanning electron microscopy and BET specific surface area test;
[0013] S1.2, the specific surface area is greater than 2048m 2 / g, and porous carbon with multiple and uniform pore sizes - commercial materials are used as raw materials for preparing electrode sheets;
[0014] S1.3. Prepare porous carbon-commercial, carbon black and PTFE solution in a mass ratio of 8:1:1 to mix and configure the loading material. Immerse the mixture in ethanol and ultrasonicate for 30-35 minutes. Use a water bath at a temperature of 75-80°C until the mixture becomes a mud-like state. Evenly spread the mud-like mixture on both sides of a 5*5cm fully dried nickel foam, and then dry and press it into sheets.
[0015] Preferably, the electrode sheet testing process is:
[0016] S2.1. Electrochemical test: The electrode sheet is subjected to electrochemical tests of cyclic voltammetry, constant current charge and discharge, and electrochemical impedance. If the test is passed, it indicates that the electrochemical properties of the electrode sheet are good;
[0017] S2.2, Cyclic stability test: After the electrode sheet undergoes ten adsorption-desorption cycles, when the capacity decay is between 10% and 15%, it indicates that the electrode sheet can be recycled.
[0018] Preferably, the composition of building the gel water absorption platform: the gel water absorption platform device consists of a conductivity meter, a 500mL beaker, a gel water absorption module, a peristaltic pump and a constant pressure source.
[0019] Preferably, the conditions of step one are set as follows: the speed of the cave pump is adjusted to 30-40 r / min, a voltage of 1.2-1.3 V is applied to the electrode sheet when the stock solution with a mass concentration of <80% is applied, and the plate spacing is set to 2±0.02 mm, and then the stock solution begins to be concentrated.
[0020] Preferably, the step 2 includes the selection of water-absorbing materials, drying of the water-absorbing materials and conducting analytical experiments, and the specific process is as follows:
[0021] S3.1. Selection of water-absorbing materials: Immerse three water-absorbing materials of the same mass, a, b, and c, in pure water for 3-3.05 hours, and find that the water absorption rate of water-absorbing material a can reach 550 times of its own, and the water absorption rate of water-absorbing material a>the water absorption rate of water-absorbing material b, and the water absorption rate of water-absorbing material a>the water absorption rate of water-absorbing material c;
[0022] S3.2, drying treatment of water-absorbing materials: put the water-absorbing materials a into the tray of the oven and dry them at a temperature of 75-80℃ for 24-25h;
[0023] S3.3. Conduct analytical experiments: Conduct analytical experiments under different concentrate temperatures, different concentrate pH values, different concentrate mass concentrations and reuse rates.
[0024] Preferably, the analytical experiment performed in S3.3 includes:
[0025] Different concentrated liquid temperatures: Divide the same mass of water-absorbing material a into 4 parts, and soak them in concentrated liquid 1 at 20℃, 25℃, 30℃, and 35℃ for 2 hours respectively. The water-absorbing material mass after swelling at 30℃ is the largest.
[0026] Different concentrated solution pH: Divide the same mass of water-absorbing material a into 4 parts, and soak them in concentrated solution 1 with pH values of 5, 7, 9, and 11 for 2 hours. The mass of the water-absorbing material after swelling is the largest when pH value is 7.
[0027] Different concentrated solution mass concentrations: Divide the same mass of water-absorbing material a into three parts and soak them in 80%, 85%, and 95% mass concentration sodium nitrate solutions for 2 hours respectively. The water-absorbing material mass after swelling is the largest when the mass concentration is 80%, and the higher the concentration, the worse the water absorption effect.
[0028] Reusability: Place the same mass of absorbent material a in 80% mass concentration concentrated solution 1 for 2 hours, weigh it to obtain its water absorption rate, and then dry it. Repeat the experiment using the dried absorbent material, and the material can be reused 5-6 times.
[0029] Preferably, the conditions of step 2 are set as follows: when the mass concentration of the concentrated solution 1 is 80%, the temperature is 30° C., and the pH is 7, the concentrated solution 1 is subjected to secondary concentration treatment.
[0030] Preferably, the step three includes the selection of a solvent and conducting an analytical experiment, and the specific process is as follows:
[0031] S4.1. Selection of solvent: ethanol is selected as solvent;
[0032] S4.2. Conduct analytical experiments: Conduct analytical experiments under the conditions of different concentrations, different amounts of solvent added, different ways of mixing solutions and solvents, different solvent addition speeds and the addition of water-absorbing materials.
[0033] Preferably, the analytical experiment process in S4.2 is:
[0034] Different concentrations: A certain proportion of ethanol solution is added to sodium nitrate solutions of different mass concentrations. The higher the mass concentration, the higher the amount of sodium nitrate crystals precipitated. When the concentration is higher than 95%, the precipitation amount tends to be flat;
[0035] Different amounts of solvent added: different amounts of anhydrous ethanol were added to 80%, 85%, 90%, and 95% mass concentration sodium nitrate solutions. When the mass ratio of anhydrous ethanol to solution was 7:1, the amount of sodium nitrate crystal precipitation was the highest.
[0036] Mixing methods of different solutions and solvents: When adding ethanol to sodium nitrate solution, the recovery rate of sodium nitrate is higher than that of adding sodium nitrate solution to ethanol. The difference between ammonium nitrate solutions with different mass concentrations is 4% to 19%;
[0037] Different solvent addition speeds: When the solvent is added to the sodium nitrate solution at different addition speeds, the amount of sodium nitrate crystals precipitated changes very little;
[0038] Addition of water-absorbing material: After the water-absorbing material is added to the sodium nitrate solution reaching the saturated precipitation amount, sodium nitrate crystals further precipitate.
[0039] Compared with the prior art, the present invention provides a method for concentrated extraction of sodium nitrate, which has the following characteristics:
[0040] Beneficial effects:
[0041] 1. The present invention uses gel water absorption technology to carry out the primary concentration of sodium nitrate, and uses the internal electrodes of the device to adsorb and desorb ions in the solution. While achieving efficient concentration, it also has the advantages of low energy consumption and good environmental protection. Then, the liquid after the gel water absorption primary concentration is secondary concentrated by using a water-absorbing gel material, so that the sodium nitrate can reach a higher concentration. Among them, the water-absorbing gel has high water absorption and selectivity, and can effectively remove water, thereby improving the purity and concentration of the solution. Finally, by adding ethanol to the concentrated solution, the solubility of sodium nitrate can be greatly reduced, and then the water-absorbing material is added to promote the crystallization of sodium nitrate. This step can not only simplify the operation process, but also ensure the high purity of the crystal. Therefore, the present invention not only improves the concentration efficiency of the sodium nitrate solution, but also takes into account the beneficial effects of simple operation, high product purity and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] See also Figure 1 , a method for concentrated extraction of sodium nitrate, comprising the following steps:
[0045] Step 1, water-absorbing gel concentration stock solution: prepare a water-absorbing gel device, use the gel water absorption method in the device to concentrate the sodium nitrate stock solution with a mass concentration lower than 80% to 80%±0.5% to obtain a concentrated solution 1. The gel water absorption technology uses electrodes to adsorb and desorb ions in the solution, which helps to achieve efficient concentration. This method has the advantages of low energy consumption and good environmental protection, and is suitable for the preliminary concentration of low-concentration sodium nitrate solutions;
[0046] Step 2, secondary concentration of water-absorbing gel: using water-absorbing gel material to secondary concentrate the concentrated solution 1 to 90%±0.10%, to obtain concentrated solution 2. By using the water-absorbing gel material to further concentrate the liquid after gel water absorption and concentration, a higher concentration can be achieved. The water-absorbing gel has high water absorption and selectivity, can effectively remove water, and improve the purity and concentration of the solution;
[0047] Step 3, dissolving and crystallizing to obtain sodium nitrate crystals: Sodium nitrate crystals are precipitated from the concentrated solution 2 by a dissolving and crystallizing method, ethanol is added to the sodium nitrate solution, and when the mass concentration of the sodium nitrate solution is 95% and the alcohol-liquid ratio is 7:1, the sodium nitrate crystals are precipitated, and then a water-absorbing material is added to further precipitate the sodium nitrate crystals. By adding ethanol to the concentrated solution, the solubility of sodium nitrate can be greatly reduced, thereby promoting its crystallization and precipitation. The method is simple to operate, has high crystal purity, and is suitable for large-scale industrial production.
[0048] Specifically, the preparation of the water-absorbing gel device in step 1 includes: preparing an electrode sheet, testing the electrode sheet, and building a gel water-absorbing platform for analysis, wherein the process of preparing the electrode sheet is:
[0049] S1.1, the porous carbon was subjected to SEM scanning electron microscopy and BET specific surface area test;
[0050] S1.2, the specific surface area is greater than 2048m 2 / g, and porous carbon-commercial materials with multiple and uniform pore sizes (micropores and mesopores) are used as raw materials for preparing electrode sheets;
[0051] S1.3. Prepare porous carbon-commercial, carbon black and PTFE solution in a mass ratio of 8:1:1 to mix and configure the loading material. Immerse the mixture in ethanol and ultrasonicate for 30-35 minutes. Use a water bath at a temperature of 75-80°C until the mixture becomes a mud-like state. Evenly spread the mud-like mixture on both sides of a 5*5cm fully dried nickel foam, and then dry and press it into sheets.
[0052] Specifically, the electrode sheet testing process is:
[0053] S2.1. Electrochemical test: The electrode sheet is subjected to electrochemical tests of cyclic voltammetry, constant current charge and discharge, and electrochemical impedance. If the test is passed, it indicates that the electrochemical properties of the electrode sheet are good;
[0054] S2.2, Cyclic stability test: After the electrode sheet undergoes ten adsorption-desorption cycles, when the capacity decay is between 10% and 15%, it indicates that the electrode sheet can be recycled.
[0055] Specifically, the components of the gel water absorption platform are as follows: the gel water absorption platform device consists of a conductivity meter, a 500 mL beaker, a gel water absorption module, a peristaltic pump and a constant pressure source.
[0056] Specifically, the conditions of step one are set as follows: the speed of the cave pump is adjusted to 30-40 r / min, a voltage of 1.2-1.3 V is applied to the electrode sheet when the stock solution with a mass concentration of <80% is applied, and the plate spacing is set to 2±0.02 mm, and then the stock solution is concentrated.
[0057] Specifically, step 2 includes the selection of water-absorbing materials, drying of the water-absorbing materials and conducting analytical experiments, and the specific process is as follows:
[0058] S3.1. Selection of water-absorbing materials: Immerse the three water-absorbing materials a, b and c of the same mass in pure water for 3-3.05h, and the water absorption rate of water-absorbing material a can reach 550 times of its own, and the water absorption rate of water-absorbing material a> water absorption rate of water-absorbing material b, and the water absorption rate of water-absorbing material a> water absorption rate of water-absorbing material c (much higher than the other two), please refer to Table 1;
[0059] S3.2, drying treatment of water-absorbing materials: put the water-absorbing materials a into the tray of the oven and dry them at a temperature of 75-80℃ for 24-25h;
[0060] S3.3. Conduct analytical experiments: Conduct analytical experiments under different concentrate temperatures, different concentrate pH values, different concentrate mass concentrations and reuse rates.
[0061] Table 1
[0062] Water-absorbent material Water absorption rate (self-multiple) a 550 b 260 c 180
[0063] Specifically, the analysis experiments performed in S3.3 include:
[0064] Different concentrated liquid temperatures: Divide the same mass of water-absorbing material a into 4 parts, and soak them in concentrated liquid 1 at 20℃, 25℃, 30℃, and 35℃ for 2 hours respectively. The water-absorbing material mass after swelling at 30℃ is the largest.
[0065] Different concentrated solution pH: Divide the same mass of water-absorbing material a into 4 parts, and soak them in concentrated solution 1 with pH values of 5, 7, 9, and 11 for 2 hours. The mass of the water-absorbing material after swelling is the largest when pH value is 7.
[0066] Different concentrated solution mass concentrations: Divide the same mass of water-absorbing material a into three parts and soak them in 80%, 85%, and 95% mass concentration sodium nitrate solutions for 2 hours respectively. The water-absorbing material mass after swelling is the largest when the mass concentration is 80%, and the higher the concentration, the worse the water absorption effect.
[0067] Reusability: Place the same mass of absorbent material a in 80% mass concentration concentrated solution 1 for 2 hours, weigh it to obtain its water absorption rate, and then dry it. Repeat the experiment using the dried absorbent material, and the material can be reused 5-6 times.
[0068] Specifically, the conditions of step 2 are set as follows: when the mass concentration of the concentrated solution 1 is 80%, the temperature is 30° C., and the pH is 7, the concentrated solution 1 is subjected to secondary concentration treatment.
[0069] Specifically, step three includes the selection of a solvent and conducting an analytical experiment, and the specific process is as follows:
[0070] S4.1. Selection of solvent: ethanol is selected as the solvent (compared with methanol, ethanol and propanol organic solvents, ethanol is non-toxic, moderately priced, miscible with water in any proportion at room temperature, and sodium nitrate is difficult to dissolve in ethanol, which meets the requirements for solvent selection);
[0071] S4.2. Conduct analytical experiments: Conduct analytical experiments under the conditions of different concentrations, different amounts of solvent added, different ways of mixing solutions and solvents, different solvent addition speeds and the addition of water-absorbing materials.
[0072] Specifically, the analytical experimental process in S4.2 is as follows:
[0073] Different concentrations: A certain proportion of ethanol solution is added to sodium nitrate solutions of different mass concentrations. The higher the mass concentration, the higher the amount of sodium nitrate crystals precipitated. When the concentration is higher than 95%, the precipitation amount tends to be flat;
[0074] Different amounts of solvent added: different amounts of anhydrous ethanol were added to 80%, 85%, 90%, and 95% mass concentration sodium nitrate solutions. When the mass ratio of anhydrous ethanol to solution was 7:1, the amount of sodium nitrate crystal precipitation was the highest.
[0075] Mixing methods of different solutions and solvents: When adding ethanol to sodium nitrate solution, the recovery rate of sodium nitrate is higher than that of adding sodium nitrate solution to ethanol. The difference between ammonium nitrate solutions with different mass concentrations is 4% to 19%;
[0076] Different solvent addition speeds: When adding the solvent to the sodium nitrate solution at different addition speeds, the amount of sodium nitrate crystals precipitated changes very little. The addition speed mainly affects the rate of crystal nucleation and the particle size distribution of the crystals.
[0077] Addition of water-absorbing material: After the water-absorbing material is added to the sodium nitrate solution that has reached the saturated precipitation amount, sodium nitrate crystals are further precipitated, and the water-absorbing material in step 2 can be reused.
[0078] Example 1
[0079] A method for concentrated extraction of sodium nitrate, characterized in that it comprises the following steps:
[0080] Step 1, concentrating the stock solution with water-absorbing gel: preparing a water-absorbing gel device, and using the gel water-absorbing method in the device to concentrate the sodium nitrate stock solution with a mass concentration of less than 80% to 82% to obtain a concentrated solution 1;
[0081] Step 2: Secondary concentration of water-absorbing gel: using water-absorbing gel material to secondary concentrate the concentrated solution 1 to 90%, thereby obtaining concentrated solution 2;
[0082] Step 3, dissolution crystallization to obtain sodium nitrate crystals: Sodium nitrate crystals are precipitated from the concentrated solution 2 by dissolution crystallization method, ethanol is added to the sodium nitrate solution, and when the mass concentration of the sodium nitrate solution is 95% and the alcohol-liquid ratio is 7:1, the sodium nitrate crystals are precipitated, and then a water-absorbing material is added to further precipitate the sodium nitrate crystals.
[0083] Comparative Example 1
[0084] Centrifugation: Centrifugation separates solid impurities from liquid in sodium nitrate solution by high-speed rotation. This method is suitable for preliminary purification of sodium nitrate solution and improving the efficiency of subsequent processing steps.
[0085] Comparative Example 2
[0086] Heating sol-gel method: The heating sol-gel method uses a combination of alkaline and acidic sodium nitrates and controls the reaction temperature to 120°C to obtain high-purity sodium nitrate crystals.
[0087] Comparative Example 3
[0088] Airflow drying method: Airflow drying method uses the power of airflow to stir sodium nitrate and volatilize nitrogen oxide at the same time, finally obtaining dry high-purity sodium nitrate.
[0089] Comparative Example 4
[0090] Cooling crystallization method: The cooling crystallization method makes sodium nitrate supersaturated by lowering the solution temperature, thereby precipitating crystals.
[0091] Comparative Example 5
[0092] Evaporation concentration method: The evaporation concentration method evaporates the water in the sodium nitrate solution by heating it to 150°C, thereby increasing the concentration of the solution.
[0093] The following is a table listing the data analysis and comparison of the purification efficiency, purity and environmental protection of Example 1 and all comparative examples:
[0094] Table 2
[0095]
[0096]
[0097] As summarized in Table 2, the method flow of Example 1 performs well in terms of purification efficiency, purity and environmental protection, while other traditional method flows in the comparative example, such as centrifugation, air flow drying and cooling crystallization, have certain limitations in purification efficiency or purity.
[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for concentrated extraction of sodium nitrate, characterized in that: The following steps are involved: Step 1, concentrating the stock solution with water-absorbing gel: preparing a water-absorbing gel device, and using the gel water-absorbing method in the device to concentrate the sodium nitrate stock solution with a mass concentration lower than 80% to 80%±0.5% to obtain a concentrated solution 1; Step 2, secondary concentration of water-absorbing gel: using water-absorbing gel material to secondary concentrate the concentrated solution 1 to 90%±0.10% to obtain concentrated solution 2; Step 3, dissolution crystallization to obtain sodium nitrate crystals: Sodium nitrate crystals are precipitated from the concentrated solution 2 by dissolution crystallization method, ethanol is added to the sodium nitrate solution, and when the mass concentration of the sodium nitrate solution is 95% and the alcohol-liquid ratio is 7:1, the sodium nitrate crystals are precipitated, and then a water-absorbing material is added to further precipitate the sodium nitrate crystals.
2. A method for concentrating and extracting sodium nitrate according to claim 1, characterized in that: The preparation of the water-absorbing gel device in step 1 includes: preparing an electrode sheet, testing the electrode sheet, and building a gel water-absorbing platform for analysis, wherein the process of preparing the electrode sheet is: S1.1, the porous carbon was subjected to SEM scanning electron microscopy and BET specific surface area test; S1.2, the specific surface area is greater than 2048m 2 / g, and porous carbon with multiple and uniform pore sizes - commercial materials are used as raw materials for preparing electrode sheets; S1.
3. Prepare porous carbon-commercial, carbon black and PTFE solution in a mass ratio of 8:1:1 to mix and configure the loading material. Immerse the mixture in ethanol and ultrasonicate for 30-35 minutes. Use a water bath at a temperature of 75-80°C until the mixture becomes a mud-like state. Evenly spread the mud-like mixture on both sides of a 5*5cm fully dried nickel foam, and then dry and press it into sheets.
3. A method for concentrating and extracting sodium nitrate according to claim 2, characterized in that: The electrode sheet testing process is as follows: S2.
1. Electrochemical test: The electrode sheet is subjected to electrochemical tests of cyclic voltammetry, constant current charge and discharge, and electrochemical impedance. If the test is passed, it indicates that the electrochemical properties of the electrode sheet are good; S2.2, Cycle stability test: After the electrode sheet undergoes ten adsorption-desorption cycles, if the capacity decay is between 10% and 15%, it indicates that the electrode sheet can be recycled.
4. A method for concentrating and extracting sodium nitrate according to claim 2, characterized in that: The components of the gel water absorption platform are as follows: the gel water absorption platform device is composed of a conductivity meter, a 500 mL beaker, a gel water absorption module, a peristaltic pump and a constant pressure source.
5. A method for concentrating and extracting sodium nitrate according to claim 1, characterized in that: The conditions of step 1 are set as follows: the rotation speed of the cave pump is adjusted to 30-40 r / min, a voltage of 1.2-1.3 V is applied to the electrode sheet of the stock solution with a mass concentration of <80%, and the plate spacing is set to 2±0.02 mm to start concentrating the stock solution.
6. A method for concentrating and extracting sodium nitrate according to claim 1, characterized in that: The step 2 includes the selection of water-absorbing materials, drying of the water-absorbing materials and conducting analytical experiments, and the specific process is as follows: S3.
1. Selection of water-absorbing materials: Immerse three water-absorbing materials of the same mass, a, b, and c, in pure water for 3-3.05 hours, and find that the water absorption rate of water-absorbing material a can reach 550 times of its own, and the water absorption rate of water-absorbing material a>the water absorption rate of water-absorbing material b, and the water absorption rate of water-absorbing material a>the water absorption rate of water-absorbing material c; S3.2, drying treatment of water-absorbing materials: put the water-absorbing materials a into the tray of the oven and dry them at a temperature of 75-80℃ for 24-25h; S3.
3. Conduct analytical experiments: Conduct analytical experiments under different concentrate temperatures, different concentrate pH values, different concentrate mass concentrations and reuse rates.
7. A method for concentrating and extracting sodium nitrate according to claim 6, characterized in that: The analytical experiments performed in S3.3 include: Different concentrated liquid temperatures: Divide the same mass of water-absorbing material a into 4 parts, and soak them in concentrated liquid 1 at 20℃, 25℃, 30℃, and 35℃ for 2 hours respectively. The water-absorbing material mass after swelling at 30℃ is the largest. Different concentrated solution pH: Divide the same mass of water-absorbing material a into 4 parts, and soak them in concentrated solution 1 with pH values of 5, 7, 9, and 11 for 2 hours. The mass of the water-absorbing material after swelling is the largest when pH value is 7. Different concentrated solution mass concentrations: Divide the same mass of water-absorbing material a into three parts and soak them in 80%, 85%, and 95% mass concentration sodium nitrate solutions for 2 hours respectively. The water-absorbing material mass after swelling is the largest when the mass concentration is 80%, and the higher the concentration, the worse the water absorption effect. Reusability: Place the same mass of absorbent material a in 80% mass concentration concentrated solution 1 for 2 hours, weigh it to obtain its water absorption rate, and then dry it. Repeat the experiment using the dried absorbent material, and the material can be reused 5-6 times.
8. A method for concentrating and extracting sodium nitrate according to claim 1, characterized in that: The conditions of step 2 are set as follows: when the mass concentration of the concentrated solution 1 is 80%, the temperature is 30° C., and the pH is 7, the concentrated solution 1 is subjected to secondary concentration treatment.
9. A method for concentrating and extracting sodium nitrate according to claim 1, characterized in that: The step three includes the selection of the solvent and the analysis experiment, and the specific process is as follows: S4.
1. Selection of solvent: ethanol is selected as solvent; S4.
2. Conduct analytical experiments: Conduct analytical experiments under the conditions of different concentrations, different amounts of solvent added, different ways of mixing solutions and solvents, different solvent addition speeds and the addition of water-absorbing materials.
10. The method for concentrating and extracting sodium nitrate according to claim 9, characterized in that: The analytical experimental process in S4.2 is as follows: Different concentrations: A certain proportion of ethanol solution is added to sodium nitrate solutions of different mass concentrations. The higher the mass concentration, the higher the amount of sodium nitrate crystals precipitated. When the concentration is higher than 95%, the precipitation amount tends to be flat; Different amounts of solvent added: different amounts of anhydrous ethanol were added to 80%, 85%, 90%, and 95% mass concentration sodium nitrate solutions. When the mass ratio of anhydrous ethanol to solution was 7:1, the amount of sodium nitrate crystal precipitation was the highest. Mixing methods of different solutions and solvents: When adding ethanol to sodium nitrate solution, the recovery rate of sodium nitrate is higher than that of adding sodium nitrate solution to ethanol. The difference between ammonium nitrate solutions with different mass concentrations is 4% to 19%; Different solvent addition speeds: When the solvent is added to the sodium nitrate solution at different addition speeds, the amount of sodium nitrate crystals precipitated changes very little; Addition of water-absorbing material: After the water-absorbing material is added to the sodium nitrate solution reaching the saturated precipitation amount, sodium nitrate crystals further precipitate.